(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the clinical outcomes of treating facial pityriasis alba with topical Tacrolimus 0.03% at the National Hospital of Dermatology and Venereology from September 2024 to August 2025. Subjects and methods: A clinical trial (interventional study with pre-post comparison and a control group) was conducted on 60 patients diagnosed with facial pityriasis alba. The intervention group (n = 30) received topical Tacrolimus 0.03%, while the control group (n = 30) was treated with topical Desonide 0.05%. The duration of treatment was 8 weeks. Results: After 8 weeks, the mean pigmentation index in the Tacrolimus group increased significantly from 59.37 to 156.72 Melanin unit, compared to an increase from 61.78 to 114.92 Melanin unit in the Desonide group (p < 0.001). Regarding lesion size, the proportion of patients achieving good to very good response was 73.3% in the Tacrolimus group, significantly higher than 16.7% in the Desonide group (p < 0.001). Adverse effects in the Tacrolimus group were mainly itching, stinging and mild burning (13.33%). No participants discontinued treatment due to adverse effects. Conclusion: Topical Tacrolimus 0.03% demonstrates significant efficacy in improving pigmentation and reducing lesion size in patients with facial pityriasis alba, with good tolerability and minimal side effects. It represents a safe and effective alternative to topical corticosteroids, especially for sensitive areas such as the face.